The Other Side of Zakat in Poverty Reduction: A Phenomenology Study - Widyatama, Arif; Baso, Andi Sabirin; Haq, Fathiatul (Ekonomi Syariah IAIN Kudus, 2020)
This study aims to understand the phenomenon of zakat given to Mustahiq. The Mustahiq uses the zakat to increase income through business development so that it can reduce poverty. The research method used is qualitative using a phenomenology approach. This study interviewed three informants who received zakat. The results of this study reveal that zakat has a different spiritual value from taxes. When zakat is distibuted, it can increase the income of the grantees. BAZNAS management system must be carried out in a professional, transparent and accountable manner and aims at eradicating poverty and unemployment in Palu with a cultural approach based on faith. Besides, it helps the poor in community. One of the goals is to create some of muzakki and awareness of helping each other.